Does forest management certification halt forest loss at country level? A global analysis - Saskia Dröge; Charline Depoorter; Axel Marx; Bart Muys (Cleaner Production Letters)
Forests play a vital role in regulating the global climate, supporting biodiversity, and sustaining the livelihoods of approximately 1.6 billion people. However, unsustainable forest management continues to drive widespread forest loss. Certification schemes such as the Forest Stewardship Council (FSC) and the Programme for the Endorsement of Forest Certification (PEFC) evolved to promote sustainable forestry practices, yet evidence of their effectiveness in reducing deforestation and forest degradation remained inconclusive. This study employed generalised additive models to assess whether increased FSC and PEFC certification coverage was associated with reduced permanent and temporary forest loss, using annual data from 2005 to 2019 across more than 113 countries while controlling for other drivers of forest change. No significant association between certification coverage and forest loss reduction was found at the country level. These findings were limited by the lack of publicly available data on certified forests at high spatial resolution and the use of aggregated country-level certification coverage, which might obscure regional (sub-country) effects. Improved transparency and finer-scale data are needed for more definitive assessments of certification's impact. Furthermore, for achieving global goals such as halting deforestation by 2030, additional strategies beyond voluntary certification are needed.